Understanding Impacts of Online Dual Practice on Health System Performance: A Qualitative Study in China - Yushu Huang; Duo Xu; Sian Hsiang-Te Tsuei; Hongqiao Fu; Winnie Yip (Taylor & Francis Group, 2023)
ABSTRACTThe outbreak of the COVID-19 pandemic has boosted the global development of online healthcare platforms. An increasing number of public hospital doctors are providing online services on private third-party healthcare platforms, creating a new form of dual practice-online dual practice. To explore the impacts of online dual practice on health system performance as well as potential policy responses, we undertook a qualitative approach that uses in-depth interviews and thematic analysis. Following a purposive sampling, we interviewed 57 Chinese respondents involved in online dual practice. We asked respondents for their opinions on the effects of online dual practice on access, efficiency, quality of care, and advice on regulatory policy. The results suggest that online dual practice can generate mixed impacts on health system performance. The benefits include improved accessibility due to increased labor supply of public hospital doctors, better remote access to high-quality services, and lower privacy concerns. It can improve efficiency and quality by optimizing patient flows, reducing repetitive tasks, and improving the continuity of care. However, the potential distraction from designated work at public hospitals, inappropriate use of virtual care, and opportunistic physician behaviors may undermine overall accessibility, efficiency, and quality. Countries should mitigate these adverse consequences via regulations that are appropriate to their healthcare system context, policy priority, and governance capacity.